(untitled) (Global Journal of Management and Business Research, 2018)
Before implementation of GST in India, Government of India collected indirect taxes in the various names. Direct tax is mostly define clearly to tax payer, but indirect tax does not define clearly because it collected by government to each stage manufacturer to customer. For clearing of indirect tax government of India introduced biggest tax reforms after independence since 1947 in the name of GST. After implementing of GST in India, there are several issues arises in front of the GOI, Professionals, business man and even customers. These are the issues highlighted in this paper.